The Hidden Values of Resisting Temptation: Effort, Meaning, and Self-Knowledge - Henden, Edmund (Ethical theory and moral practice, 2025)
Self-control is generally regarded as a valuable capacity. However, the value of directly resisting temptations (a central part of our commonsense notion of self-control) has recently come under attack. Directly resisting temptations - as opposed to avoiding them - has been claimed to have several drawbacks, such as being an inefficient way of dealing with temptations, not contributing to an agent’s well-being, or even causing harmful "mental fragmentation." In fact, some claim that most or all of the values of self-control can be achieved, not by struggling to directly resist temptations, but rather by steering clear of them. In this paper, we seek to push back against this trend. We argue that there are specific values attached to directly resisting temptations that cannot be secured by avoiding them. Drawing on recent psychological evidence, we suggest that a significant part of the value of ‘direct resistance’ is grounded in the fact that it involves the exertion of effort. Due to this feature, we contend, directly resisting temptations can both make our activities feel more meaningful and provide us with a valuable form of self-knowledge.